The Effects of Training and Communication: Study on Performance of the Food and Beverage Service Employee - Sulastri, Ida Ayu Putu (Akademi Komunitas MAPINDO, 2023)
Job training and communication are the basis for employees to be able to develop their personalities and be responsible for their positions. This study aims to analyze the effect partially and simultaneously between training and communication on employee performance in the food and beverage department at Padma Resort Legian. This study uses a questionnaire in data collection. The number of samples used were 37 people. Data analysis techniques used were descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test analysis, and f-test analysis. The results of the analysis show the regression equation model Y=0.529 + 0.832 X1 + 0.527 X2. This study resulted in three conclusions, namely (a) there is a positive and significant influence between training on employee performance. This is indicated by the significance value for the training variable (X1) of 0.000 t table (0.05 : 34) = 1.691; (b) there is a positive and significant influence between communication on employee performance. This is indicated by the significance value for the communication variable (X2) of 0.000 t table (0.05 : 34) = 1.691; (c) there is a positive and significant influence between training and communication on employee performance. This is indicated by the significance value of 0.000 F table 3.276. Keywords: Training, Communication, Employee PerformanceKeywords: Training, Communication, Employee Performance